Annual Survey of Governments, 1983: Employment Statistics ([Verlag nicht ermittelbar], 1986)
State and local government employment data are provided in this file. Full- and part-time employment, full-time equivalency, and payroll statistics are included. Data are supplied by type of government and by function. Governmental functions include education, police and fire protection, financial and central administration, judiciary, utilities, public welfare, parks and recreation, health care, transit, and natural resources. Standard Metropolitan Statistical Area (SMSA) codes are given for local governments in metropolitan areas.